APPROXIMATION OF DISTRIBUTION OF INFORMATIVE PARAMETERS FOR NON-DESTRUCTIVE CONTROL OF COMPOSITE MATERIALS - Єременко, В.; Суслов, Є.; Сунетчієва, С. (Science-based technologies, 2012)
The article describes the data processing method in impedance non-destructive testing of aerospace oriented composite materials. The way to fitting nonnormal statistical distribution of experimental data is reviewed. Experimental results and data processing method have shown.